Teeth and Covariates: Association with Risk of Falls - Shivani Kohli; Aaron Lam Wui Vun; Christopher Daryl Philip; Cassamally Muhammad Aadil; Mahenthiran Ramalingam (International Journal of Dentistry)
Purpose. Falls occur commonly in geriatric populations and undesirably influence their life, morbidity, and mortality. The aim of this study was to analyze the association between the number of teeth present among the elderly population and covariates in relation to the risk of falls. Materials and Methods. This study was conducted at various old age homes in the Klang Valley region of Malaysia involving the geriatric population aged 60 years and above. A detailed questionnaire consisting of sociodemographic data including sex, age, household income, and dental variables such as the number of teeth and chewing difficulty was obtained. The Tinetti test (TT) was used to evaluate the patients’ ability to walk, to maintain postural balance, and to determine their risk of falling. The short version of the Geriatric Depression Scale was used to assess depression among the participants, and the Barthel Scale was used to analyze the subject’s ability to perform the activities of daily living (ADL). Results. Statistically significant association was observed in relation to the number of teeth present and risk of falls (p<0.05). Subjects who had 19 teeth or less in total had moderate to highest risk of falls (p=0.001) in comparison with subjects who had 20 teeth or more. Those aged 70 years and above showed the highest risk of falls (p=0.001) in comparison with the subjects aged between 60 and 69 years. Subjects with depression (p=0.03) and presence of illness related to fall showed statistically significant difference (p=0.001) in comparison with those who did not suffer from the same. Compromised ADL (p=0.001) (which included ability to perform several tasks like indoor mobility, climbing stairs, toilet use, and feeding) and low monthly income (p=0.03) was also observed among subjects who had higher risk of falls. Conclusion. According to the results achieved, there was a high statistically significant association observed between the number of teeth present, age, depression, ADL, and presence of illness in relation to the risk of falling among the geriatric population. Henceforth, oral rehabilitation of elderly patients with less number of teeth may reduce their risk of falls.